Matrix effect on butyltin analysis of sediments and fish tissues by GC-PFPD - Dos Santos, Dayana M. [UNESP]; Marchi, Mary Rosa Rodrigues de [UNESP]; Godoi, Ana Flávia L.; Turra, Alexander; Montone, Rosalinda C. (Sociedade Brasileira de Quimica (SBQ), 2013)
Butyltin (BTs) quantification in environmental matrices can be affected by interfering species found primarily in complex matrices,such as sediment and biota tissues. This study investigated matrix effects in analytical procedures for butyltin (TBT,DBT and MBT) quantification and speciation in sediments and in two fish tissues (gill and liver) by gas chromatography with pulsed flame photometric detection (GC-PFPD) analysis. Unlike sediment samples,tissues exhibited a significant matrix effect,thus,the quantification should be made by curve over matrix to avoid quantification errors and loss of analytical accuracy. © 2013 Sociedade Brasileira de Química.
Keywords: Biota tissues; Butyltin; GC-PFPD; Matrix effect; Sediment